Meningkatkan Keterampilan Motorik Kasar Anak Melalui Permainan Menjala Ikan Di TK Raudhatul Ulum Siasam - Desi Puspita Sari; Melvi Lesmana Alim; Yenda Puspita; Moh. Fauziddin; Joni Joni (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to determine the improvement of gross motor skills through fish netting games in kindergarten children at Raudhatul Ulum Siasam, Balung Village, XIII Koto Kampar District. This research is a classroom action research (CAR). Data collection methods used observation, documentation, and interviews. The data analysis technique was conducted descriptively and quantitatively, by calculating the percentage of achievement in children's gross motor development for each cycle. The results of the study showed an improvement in children's gross motor skills after participating in the fish netting game activities. In the pre-action stage, most children were still in the